THE FACTORS AFFECTING FERTILITY WIFE FISHERMEN IN DISTRICT BATANG TUAKA INDRAGIRI HILIR - Ningsih, Dini Syafitri; Hamid, Hamdi; Nugroho, Firman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study research conducted in April 2016 in District Batang Tuaka Indragiri Hilir. This study aims to determine: 1) the effect of household income toward fishermen wife fertility in District Batang Tuaka Indragiri Hilir, 2) the influence of husband and wife education toward the fishermen wife fertility in District Batang Tuaka Indragiri Hilir, 3) the influence of working time toward the fishermen wife fertility in District Batang Tuaka Indragiri Hilir, 4) the effect of the first marriage age of fertility wife fishermen in District Batang Tuaka Indragiri Hilir, 5) the effect of contraceptives using toward the fishermen wife fertility in District Batang Tuaka Indragiri Hilir. The method used in this reseacrh was survey method, with 76 respondents. Consisting of two villages namely Sungai Luar were 42 couples and 34 married couples Sungai Piring. Based on the research results of this study concluded that: Family income variable (X1) significantly affects the fisherman's wife Fertility in District Batang Tuaka Indragiri Hilir, Respondents' education level variable (X3) significantly affects the fisherman's wife Fertility in District Batang Tuaka Indragiri Hilir, Variable working time hours (X4) significantly affects the fisherman's wife Fertility in District Batang Tuaka Indragiri Hilir, The variable age at first marriage (X5) did not significantly influence the Fisherman's wife Fertility in District Batang Tuaka Indragiri Hilir, Variable duration of use of contraceptives (X6) significantly affects the fisherman's wife Fertility in District Batang Tuaka Indragiri Hilir Keyword : Factors, Fertility, Firsheman Wife, Batang Tuaka